Bioartificial Articular Cartilage Substitute (BACS): today’s innovation for active tomorrows - Abdul Rahman, Rozlin; Sha'ban, Munirah; Zulkifly, Ahmad Hafiz; Che Ahmad, Aminudin; Hashi, Abdurezak Abdulahi; Abdul Rahman, Suzanah (2016)
BACS: Applying the principle of “Tissue Engineering Triad”